Factors influencing suicidal ideation among female late adolescents from a Korean rural province - Hae Kyung Jo; Hyun Kyoung Kim (Korean Society of Women Health Nursing, 2020)
Purpose This study aimed to examine factors affecting suicidal ideation among female late adolescents from a Korean rural province. Methods A descriptive cross-sectional design involving self-reported questionnaires was used. The data were collected from female adolescents aged 18 to 22 years, from high schools, universities, churches, and local community centers. The sample consisted of 197 female late adolescents from three rural areas in Korea. The Center for Epidemiological Studies-Depression Scale and the Suicidal Ideation Scale were used to measure depression and suicidal ideation, respectively. Results Suicidal ideation was correlated with having a specific suicide plan (r=.65, p<.001), depression (r=.39, p<.001), subjective well-being (r=-.46, p<.001), ever experienced violence (r=.15, p=.029), and age (r=-.21, p=.003). Factors affecting suicidal ideation among rural female adolescents were having a specific suicide plan (β=.56, p<.001), subjective well-being (β=-.23, p=.001), and suicide of a close person (β=.12, p=.035). These factors explained 48.0% of the variance in suicidal ideation (F=37.62, p<.001). Conclusion This study demonstrated that affective factors and personal experiences regarding suicide were critical indicators for suicidal ideation among female late adolescents. These factors should be managed and tailored nursing should be offered to prevent suicide and enhance the psychiatric health of female late adolescents.